Switching on/off aryl hydrocarbon receptor and pregnane X receptor activities by chemically modified tryptamines - Sládeková, Lucia; Zgarbová, Eliška; Vrzal, Radim; Vanda, David; Soural, Miroslav; Jakubcová, Klára; Vázquez-Gómez, Gerardo; Vondráček, Jan; Dvořák, Zdeněk (Toxicology letters, 2023)
Microbial indoles have been demonstrated as selective or dual agonists and ligands of the pregnane X receptor (PXR) and aryl hydrocarbon receptor (AhR). However, structural determinants of microbial indoles selectivity towards both receptors remain elusive. Here, we studied the effects of existing and newly synthesized derivatives of indole microbial metabolite tryptamine on the activity of AhR and PXR receptors. We show that the elongation of indolyl-3-alkaneamine chain, indole N-methylation and conversion of indolyl-3-alkaneamines to oleamides resulted in a major increase of PXR activity and in parallel loss of AhR activity. Using reporter gene assays, RT-PCR and TR-FRET techniques, we have characterized in detail the activation of PXR by novel indolyl-3-alkanyl-oleamides, 1-methyltryptamine and 1-methyltryptamine-acetamide. As a proof of concept, we demonstrated anti-inflammatory and epithelial barrier-protective activity of lead derivatives in intestinal Caco-2 cells, employing the measurement of expression of pro-inflammatory chemokines, tight junction genes, trans-epithelial electric resistance TEER, and dextran-FITC permeability assay. In conclusion, we show that a subtle chemical modifications of simple microbial indole metabolite tryptamine, leads to substantial changes in AhR and PXR agonist activities.
Keywords: Tryptamine; pregnanový X receptor; Indoles; tryptaminy; Caco-2 buňky; Humans; Aryl hydrocarbon receptor; lidé; Pregnane X Receptor; indoly; receptory aromatických uhlovodíků; Receptors, Aryl Hydrocarbon; Tryptamines; Receptors, Steroid; Microbial indoles; Caco-2 Cells; Pregnane X receptor; steroidní receptory